Phytochemicals from fruit and vegetable waste generated in hotels: Optimization of recovery procedure and potential for value-addition. (1st May 2022) - Srivastava, Varsha; Balakrishnan, Malini
Graphical abstract: Highlights: Fruit and vegetable waste generation data collected through survey of hotels. Model mixed waste composed based on hotels survey data. Optimized phytochemicals extraction procedure from model mixed waste. Phytochemicals recovered–polyphenols, flavonoids, flavones/flavonols and flavanol. Phytochemicals with high market value identified and quantified. Abstract: Fifteen star-category hotels in the National Capital Region of India were surveyed to assess the mixed fruit and vegetable waste generated. Based on the survey, a model mixed waste was prepared and used to identify the optimal procedure for recovery of bioactive phytochemicals and Trolox equivalent antioxidant capacity (TEAC) followed by preliminary identification of phytochemical constituents. The optimization procedure was done over (i) level I focusing on sample type (fresh, oven dried, vacuum dried), extraction technique (maceration, ultrasound assisted extraction), removal of interfering components by treatment with dichloromethane (DCM) and extraction in different solvents, and (ii) level II focusing on solvent concentration and extraction time, in both non DCM and DCM treated samples. The model mixed waste consisted of peels of pineapple, papaya, potato, pomegranate, apple, onion and citrus. The optimal conditions for recovery of phytochemicals and TEAC were non DCM treated vacuum dried samples subjected to ultrasonic assisted extraction for 60 min using ∼ 63% acetone. This resulted in recovery of appreciable amounts of total extractable phytochemicals consisting of polyphenols and flavonoids as the major components with relatively smaller amounts of flavones and flavanols. High TEAC values were obtained with both aqueous phase (ABTS) and organic phase (DPPH) assays. Preliminary investigation revealed the presence of various high-value compounds particularly gallic acid, ferulic acid, rutin and catechin in the phytochemicals extract. Consequently, there is significant potential to recover value-added phytochemicals from mixed fruit and vegetable waste from hotels contributing towards a circular bioeconomy.